THE QUALITY OF HEALTH SERVICES OF CORONA VIRUS DISEASE 2019 (COVID-19) PATIENTS TREATED IN THE ISOLATION ROOM OF UNDATA REGIONAL HOSPITAL OF PALU, CENTRAL SULAWESI PROVINCE - Zulkipli, Zulkipli; Suardi, Suardi; Sutomo, Maskuri (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2022)
This study aims to determine the quality of health services of COVID-19 patients treated in the Isolation Room of the Undata Hospital of Palu, Central Sulawesi Province. This research is a descriptive and qualitative research. Data collection techniques through in-depth interviews with 10 informants consisting of Covid-19 patients who had been treated in the Isolation Room of the Undata Hospital of Central Sulawesi Province totaled five (5) people and the manager of the Undata Hospital of Central Sulawesi Province totaled five (5) people. The data analysis method in this study uses triangulation techniques and theanalysis tool software NVIVO 12 Plus. The results of this study indicate that . Quality of Health Services For Covid-19 patients who are being treated in the Isolation Room of the Undata Hospital, Central Sulawesi Province in Palu, which consists of Tangible (physical evidence), Reliability (reliability), Responsiveness (responsiveness), Assurance (guarantee), and Empathy (empathy). ) shows good quality in accordance with the expectations of Covid-19 patients, which is supported by regulatory factors, organizational factors, work skills factors and infrastructure factors, but there is still a need to improve and improve the quality of patient room comfort, discipline of officers in the service process, response of officers in the process service, punctuality in service and guarantee on time in service even though the reliability and empathy of the officers are very good. Keywords: Quality, Service, Health, Patient, Covid-19, ever treated